COVID-19 vaccine effectiveness and variants in Nepal: study protocol for a test-negative case-control study with SARS-CoV-2 genetic sequencing - Bijukchhe, SM; O'Reilly, PJ; Theiss-Nyland, K; Gurung, M; Pokhrel, B; Kelly, S; Acharya, S; Maharjan, S; Shrestha, A; Pandey, B; Lama, M; Shrestha, I; et al. (BMJ Publishing Group, 2023)
INTRODUCTION: Inactivated, viral vector and mRNA vaccines have been used in the Nepali COVID-19 vaccination programme but there is little evidence on the effectiveness of these vaccines in this setting. The aim of this study is to describe COVID-19 vaccine effectiveness in Nepal and provide information on infections with SARS-CoV-2 variants.